(untitled) (University of Khartoum Engineering Journal, 2022)
Symmetric encryption algorithms are widely used in the field of information security due to the rapid increasing need to pass information via computer networks and communication technology. All symmetric algorithms are commonly used the same key for encryption and decryption. Triple-Data Encryption algorithm TDEA is a type of symmetric encryption methods. The proposed algorithm consists of triple-keys used through three stages of single round DES design. The proposed implementation in this paper is optimized in terms of chip area and performance speed. The results are concluded in terms of chip area performance and performance per area. The comparison results with similar encryption algorithms are satisfying and very competitive.